IMPLICATIONS OF URBAN LAND USE LAND COVER CHANGE ON LAND SURFACE TEMPERATURE AND THERMAL COMFORT: THE CASE OF ADDIS ABABA, ETHIOPIA. - Abraha, Gebru Zereabiruk; Arsiso, Bisrat Kifle (Journal of Urban Development Studies, 2023)
Environmental domains such as surface temperature and accompanying thermal stress were most affected and will continue to be affected by the replacement of natural terrains with impervious surfaces (urban growth). GIS and remote sensing techniques are now receiving a lot of interest in detecting and analyzing such domains. This study examined the thermal comfort of the city using multispectral satellite images taken between 1991 and 2022. To analyze and display data in this study, applications such as ArcGIS 10.7, ERDAS IMAGINE2013, and Excel 2013 were used. Between 1991 and 2022, vegetation cover, agricultural land, and bare land lost a net of 54%, 28%, and 31%, respectively, while built-up land gained a net of 113%. Over the previous three decades, while the city's mean annual surface temperature has risen by 0.27oC. Furthermore, whereas land surface temperature and built-up areas are positively related, vegetation in the city is negatively related to land surface temperature. In 1991, 305.5 km2 (57%) and 233.67 km2 (43% of the study area fell into the excellent and worst ecological categories, respectively, while in 2022, approximately 244.46 km2 (43%) and 294.7 km2 (55%) of the city area's geographical coverage fall into the excellent and worst thermal condition categories, respectively. Overall, the city's thermal stress has grown during the last three decades. Appropriate techniques are necessary to boost the city's vegetation cover.